2015
DOI: 10.18632/oncotarget.5314
|View full text |Cite
|
Sign up to set email alerts
|

FXR induces SOCS3 and suppresses hepatocellular carcinoma

Abstract: Suppressor of cytokine signaling 3 (SOCS3) is regarded as a vital repressor in the liver carcinogenesis mainly by inhibiting signal transducer and activator of transcription 3 (STAT3) activity. Farnesoid X Receptor (FXR), highly expressed in liver, has an important role in protecting against hepatocellular carcinoma (HCC). However, it is unclear whether the tumor suppressive activity of FXR involves the regulation of SOCS3. In the present study, we found that activation of FXR by its specific agonist GW4064 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 47 publications
(48 reference statements)
3
37
0
Order By: Relevance
“…Tumours in the liver are at the same time exposed to the potent agonistic effects of FXR. Several reports have suggested that direct FXR stimulation of tumours poses no oncological concerns, and the increase in circulating FGF‐19 levels induced by OCA is not expected to increase the growth of tumours expressing Fgfr4. Pharmacological safety studies in mice have revealed that 2 years' exposure to a dose (25 mg per kg per day) exceeding that used in the present study and in ongoing clinical trials did not result in OCA‐related neoplasms (personal communication; L. Adorini, Intercept Pharmaceuticals, based on the toxicology report by WIL Research, Ashland, Ohio, USA).…”
Section: Discussionmentioning
confidence: 65%
“…Tumours in the liver are at the same time exposed to the potent agonistic effects of FXR. Several reports have suggested that direct FXR stimulation of tumours poses no oncological concerns, and the increase in circulating FGF‐19 levels induced by OCA is not expected to increase the growth of tumours expressing Fgfr4. Pharmacological safety studies in mice have revealed that 2 years' exposure to a dose (25 mg per kg per day) exceeding that used in the present study and in ongoing clinical trials did not result in OCA‐related neoplasms (personal communication; L. Adorini, Intercept Pharmaceuticals, based on the toxicology report by WIL Research, Ashland, Ohio, USA).…”
Section: Discussionmentioning
confidence: 65%
“…FXR is highly expressed in liver and has an important role in protecting against HCC by inhibiting cell growth and inducing cell cycle arrest at G1 phase (49). Genomic analysis also identified HNF4a, a major hepatocytic transcription factor, as the main upstream regulator in liver and other liver specification genes upregulated in liver and tumor, suggesting that C188-9 induced hepatocytic differentiation in both liver and tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the stimulation of growth of renal adenocarcinoma cells by FXR ligand may arise from the down-regulation of p53 translation in a miR-21-dependent manner. There are several reports that state FXR regulates the proliferation of hepatocellular and other carcinoma cells (Zhang et al, 2012;He et al, 2015;Guo et al, 2015;Guan et al, 2013;Xie et al, 2016). Zhang et al (2012) and He et al (2015) have reported FXR inhibits the proliferation of hepatocellular carcinoma cell line HepG2 based on the data showing FXR ligand GW4064 reduced the value of MTT assay.…”
Section: Fxr Down-regulates the Expression Of P53 In Renal Adenocarcimentioning
confidence: 99%
“…Thus, in these cells treated with the FXR ligand, the value of MTT assay does not reflect proliferation. Guo et al (2015) have also reported the FXR ligand inhibits the proliferation of HepG2 cells by showing cell cycle arrest caused by the FXR ligand, however, they performed the FXR ligand treatment in the medium containing very low concentration of FBS. Since our previous study in HepG2 cells (Fujino et al, 2012) and the present study have been performed in the medium containing 10% FCS sufficient for cell growth, our data is not comparable with the data obtained from Guo et al Consistent with our previous study (Fujino et al, 2012), Xie et al (2016) have reported FXR ligand GW4064 stimulates cell proliferation of HepG2 cells by analyzing DNA synthesis.…”
Section: Fxr Down-regulates the Expression Of P53 In Renal Adenocarcimentioning
confidence: 99%